Perbandingan Peramalan Permintaan Produk Hollow Alumunium Menggunakan Metode Single Moving Average Dan Exponential Smoothing Pada PT. MU - Reza Septiansyah; Wahyudin Wahyudin (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Demand forecasting is an attempt to predict demand for a product or prepare stock for a certain time. PT MU is an aluminum distribution company that sells products in the form of white powder coating white aleksindo, sells hikarindo aluminum window materials, curved aluminum frame materials, aluminum door frame materials wood veins and also as a center for making aluminum door frames. The demand for Hollow Aluminum at PT MU from month to month during 2022 has increased and also decreased. Therefore the company conducts demand forecasting. The method used in forecasting Hollow Aluminum demand is to compare the single moving average and exponential smoothing methods to find out the most effective method. Based on the results of data processing and discussion, it is obtained that the most effective method in forecasting Hollow Aluminum products is the 3-month single moving average method because it obtains the lowest mean squared error (MSE) value of 392.67. Keywords: Exponential Smoothing, Forecasting and sales, Single Moving Average